Influences of Aflatoxin B1 on main intestinal bacteria communities and enzyme activities in mice. (3rd April 2019) - He, Lu; Liu, Yawei; Guo, Yanfang; Xiao, Nenqun; Tan, Zhoujin
Abstract: Intestine microbiota and enzyme activities have crucial effects on host's health and behavior. In order to provide evidences for the toxicology of Aflatoxin B1 (AFB1 ) on human's health objectively, the influence of AFB1 on intestine microbiota and enzyme activities was conducted. Thirty-two Kunming mice were randomly placed into control group, low-dosage group, middle-dosage group, and high-dosage group after being fed for 4 days adaptively. Then they were fed intragastrically with 0.4 mL of 0 mg/L, 2.5 mg/L, 4 mg/L, and 10 mg/L of AFB1 solutions, twice a day for 62 days. Following this, the intestine contents were collected and the microorganisms and enzyme activities were analyzed. The results showed that the number of bacteria in the low-dosage ( p  = .024), the middle-dosage ( p  = .016) and the high-dosage ( p  = .000) groups and the number of Bifidobacterium spp. in the high-dosage group ( p  = .001) increased significantly in comparison with the control group. Compared to the control group, the activities of amylase in all AFB1 groups increased significantly ( p  = .000), the activities of xylanase ( p  = .005) and cellulase ( p  = .002) increased also in the high-dosage group. These results indicated that AFB1 destroyed the intestinal microecological balance and increased the activities of intestinal enzymes, but there were no significant effects on the weight of mice.